1978
DOI: 10.1002/aic.690240111
|View full text |Cite
|
Sign up to set email alerts
|

A formulation for ϵM and ϵH based on the surface renewal principle

Abstract: To = maximum temperature to which char has been exposed previous to gasification in IGT kinetic scheme 2 Superscript o c = condition in the bulk phase = condition at the core surface = condition at the transition between gasification = condition at the top of the reactor = condition at the gas inlet = condition at the core surface and combustion zone This paper presents a simplified formulation for Elf for low to moderate Prandtl number fluids and for E, , , that utilizes the surface renewal model, but which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These models can be broadly classified as the film penetration models, 70,71 growth breakdown models or periodic viscous sublayer models, 20,23,72-74 RSR models, [75][76][77] and surface rejuvenation models. [78][79][80][81][82][83] The details of these models can be obtained from Sideman and Pinczewaski 17 and Thakre and Joshi. 3 4.2.2.…”
Section: Theories Based On the Turbulent Shear Stress Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…These models can be broadly classified as the film penetration models, 70,71 growth breakdown models or periodic viscous sublayer models, 20,23,72-74 RSR models, [75][76][77] and surface rejuvenation models. [78][79][80][81][82][83] The details of these models can be obtained from Sideman and Pinczewaski 17 and Thakre and Joshi. 3 4.2.2.…”
Section: Theories Based On the Turbulent Shear Stress Approachmentioning
confidence: 99%
“…This "surface rejuvenation concept" formed the basis for the development of several models. [79][80][81][82][83] Harriott 78 proposed a random eddy modification of the penetration theory. He noted that the main error in the previous theories was the assumption that the eddies that influence the transfer rate come all the way to the wall.…”
Section: Surface Rejuvenation Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent paper, the kinetics of cobalt diffusion out of cobalt-hardened gold electroplate was reported (1). In that study, at temperatures above ~150~ in dry air, Auger electron spectroscopy indicated the presence of potassium on the cobalt oxide film surface.…”
mentioning
confidence: 97%